TIPOLOGI PENGHUNI KAWASAN PENGEMBANGAN PERUMAHAN PINGGIRAN KOTA PEKANBARU (FENOMENA PEKANSIKAWAN) - Juliani "; Yusmar Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The title of this research is a typology Residents Housing Development Zone Suburbs Pekanbaru (Phenomenon Pekansikawan) .Penelitian aims to determine (1) How Occupants Characteristics Housing Development Zone Suburbs Pekanbaru. (2) What factors are affecting the occupants preferences in choosing Housing Housing Development Zone Suburbs Pekanbaru. The subjects were all residents in the Griya Sakti Km-9 subdistricts Tapung Kampar regency. The population in this research were 604 houses, the number of samples taken 61 people. Samples were taken with strafied proportionate random sampling technique. This research was conducted in a suburban area of Pekanbaru Precisely at Griya Sakti-9 Km Desa Indah Karya Tapung District of Kampar regency. The reasons to vote for a residential housing is the furthest to the facilities is still low, but many devotees. This research method is quantitative descriptive and quantitative associative. To collect data the researchers used questionnaires and documentation.The chi square test results showed that the behavioral variables influence consumer preference (priority) occupants with indicators that influence the personal factors (economy) and psychological factors (motivation pekansikawan, live better perception). X2 made natural factors affect the occupant preferences are personal factors (personal place and breeding ground for children and investments) and offers developers (credit prices stable and dp (money first) costKeywords: consumer behavior, natural and artificial factors, preferences